If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(9 + -3x) = -5(2x + -1) + 8(3x + 2) 8 + (9 * -1 + -3x * -1) = -5(2x + -1) + 8(3x + 2) 8 + (-9 + 3x) = -5(2x + -1) + 8(3x + 2) Combine like terms: 8 + -9 = -1 -1 + 3x = -5(2x + -1) + 8(3x + 2) Reorder the terms: -1 + 3x = -5(-1 + 2x) + 8(3x + 2) -1 + 3x = (-1 * -5 + 2x * -5) + 8(3x + 2) -1 + 3x = (5 + -10x) + 8(3x + 2) Reorder the terms: -1 + 3x = 5 + -10x + 8(2 + 3x) -1 + 3x = 5 + -10x + (2 * 8 + 3x * 8) -1 + 3x = 5 + -10x + (16 + 24x) Reorder the terms: -1 + 3x = 5 + 16 + -10x + 24x Combine like terms: 5 + 16 = 21 -1 + 3x = 21 + -10x + 24x Combine like terms: -10x + 24x = 14x -1 + 3x = 21 + 14x Solving -1 + 3x = 21 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -1 + 3x + -14x = 21 + 14x + -14x Combine like terms: 3x + -14x = -11x -1 + -11x = 21 + 14x + -14x Combine like terms: 14x + -14x = 0 -1 + -11x = 21 + 0 -1 + -11x = 21 Add '1' to each side of the equation. -1 + 1 + -11x = 21 + 1 Combine like terms: -1 + 1 = 0 0 + -11x = 21 + 1 -11x = 21 + 1 Combine like terms: 21 + 1 = 22 -11x = 22 Divide each side by '-11'. x = -2 Simplifying x = -2
| 4v+17=89 | | -8x=17+8 | | 10/9=3/9 | | z/=6 | | -4x+111=87 | | 100x+6= | | 3x-3+8=4x+2 | | x^2-14x=176 | | 7x+22=9x+10 | | 4K-2m+k= | | 7n+4n=-11 | | 4(-3x+6)=(-2x+4) | | 9g-2g-5g=16 | | 11+8x+19=20x+6 | | 0.03+0.08+0.7=0.2 | | 14t+-14t-t=18 | | W-22=31 | | X^4-4x^3+16x-16= | | 2x+3-5+2=4x*5 | | 4n+4+5=8 | | -2p-3(3-3p)=4(p-2)-22 | | 15*15=X^2+x^2 | | 3u+16=40 | | 3cosx+4sinx+7=0 | | (9x-8)+8= | | 42*42=(20.4*20.4)+x^2 | | 2x-6+x=42 | | (5x+7)+(-2x+2)= | | a-6=16+6a | | (3x-5)+y=27 | | 12/8=x | | 3j^2-30j+12=0 |